2022
DOI: 10.1371/journal.pone.0263403
|View full text |Cite
|
Sign up to set email alerts
|

The global, regional, and national burden and quality of care index (QCI) of colorectal cancer; a global burden of disease systematic analysis 1990–2019

Abstract: Background Colorectal cancer (CRC) is among the five most incident and lethal cancers in world and its burden varies between countries and sexes. We aimed to present a comprehensive measure called the quality of care index (QCI) to evaluate the inequity and healthcare quality of care regarding CRC by sex and location. Methods Data on the burden of CRC were extracted from the Global Burden of Disease study 2019. It was transformed to four ratios, including mortality-to-incidence, disability-adjusted life year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Based on the up-to-date data from the Global Burden of Disease (GBD) Study 2019, [ 6 , 7 , 8 ] we systematically reported the incidence, deaths, and DALYs of EoCRC and its risk factors at the global, regional, and national levels in relation to year, age, sex, geographic location, and sociodemographic index (SDI) from 1990 to 2019. Although the burden of CRC and its risk factors based on GBD 2019 have been well estimated [ 9 , 10 , 11 , 12 ], there is no one study focusing specifically on EoCRC. To our knowledge, this study is the first to investigate the burden of EoCRC and its risk factors based on the latest data from the GBD 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the up-to-date data from the Global Burden of Disease (GBD) Study 2019, [ 6 , 7 , 8 ] we systematically reported the incidence, deaths, and DALYs of EoCRC and its risk factors at the global, regional, and national levels in relation to year, age, sex, geographic location, and sociodemographic index (SDI) from 1990 to 2019. Although the burden of CRC and its risk factors based on GBD 2019 have been well estimated [ 9 , 10 , 11 , 12 ], there is no one study focusing specifically on EoCRC. To our knowledge, this study is the first to investigate the burden of EoCRC and its risk factors based on the latest data from the GBD 2019.…”
Section: Introductionmentioning
confidence: 99%
“…More details of the protocol used in generating QCI based on DALYs, mortality, prevalence, incidence, YLLs, and YLDs ratios have been fully elaborated elsewhere (Mohammadi et al, 2020). This method has been previously employed in various papers to demonstrate QCI in different diseases, including endocarditis (Momtazmanesh et al, 2022), ischemic heart disease (Aminorroaya et al, 2022), liver cancer (Ghamari et al, 2022), pancreatic cancer (Aryannejad et al, 2021), colorectal cancer (Nejadghaderi et al, 2022), thyroid cancer (Azadnajafabad et al, 2021), brain and other central nervous system (CNS) cancers (Mohammadi et al, 2021), gallbladder and biliary tract cancer (Khanali et al, 2021), lip and oral cavity cancer (Sofi-Mahmudi et al, 2021), child and adolescents (Hanifiha et al, 2022), non-rheumatic valvular heart diseases (Nejad et al, 2022), and hematologic malignancies (Keykhaei et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Calculation details and codes of QCI are available in a published protocol 26 . Also, other published articles utilizing the QCI to evaluate quality of care are available to prove the efficacy of this proxy 27‐38 . In summary, QCI is generated from the integration of four indices of mortality to incidence ratio (MIR), DALYs to prevalence ratio, prevalence to incidence ratio, and YLLs to YLDs ratio compiled by the principal component analysis (PCA) method 39 .…”
Section: Methodsmentioning
confidence: 99%
“… 26 Also, other published articles utilizing the QCI to evaluate quality of care are available to prove the efficacy of this proxy. 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 In summary, QCI is generated from the integration of four indices of mortality to incidence ratio (MIR), DALYs to prevalence ratio, prevalence to incidence ratio, and YLLs to YLDs ratio compiled by the principal component analysis (PCA) method. 39 The QCI scores are scaled into 0 to 100, as higher scores indicate better quality of care.…”
Section: Methodsmentioning
confidence: 99%